Characteristics of pedestrians descending on a stairway: A trajectory-based empirical analysis. (April 2023) - Ye, Rui; Fang, Zhiming; Zeng, Guang; Wang, Qiao; Lian, Liping; Cao, Shuchao
Highlights: Microscopic movement characteristics of pedestrians on the stairs are analyzed. Pedestrian lane formation on the stairs is quantified. Spatial characteristic of the nearest neighbor on the stairs is investigated. Pedestrian individual fundamental diagram on the stairs is derived. The degree of congestion and intrinsic risk for stair movements is measured using congestion level and crowd danger. Abstract: In this paper, we make a systematic analysis on movement characteristics of descending pedestrians on a stairway. According to the clustering of pedestrian lanes, the average distance between two adjacent lanes is 0.52 m under four-lane condition, while it is 0.64 m under three-lane condition. The innermost lane is found to be narrower than other lanes when the density is relatively high. With the decrease of density, the spatial distribution of the nearest neighbor becomes less condensed and its shape also gets more elliptical. On the stairs pedestrians sometimes allow the nearest neighbor to be in the front and back, while on level ground they tend to avoid the nearest one being located in these positions. Along the movement direction, pedestrian speed will first increase and then decrease, and then on the last tread before reaching the stair landing, there will be a sudden increase of speed. According to the individual fundamental diagram, the speed on the stairs is significantly lower than that on level ground, but the speed difference will become smaller with the increase of density. The values of congestion level and crowd danger are larger on the stairs than on level ground when the density is higher than 1.4 ped/m 2 . This demonstrates that movements on the stairs are more dangerous than those on level ground. It is hoped that the results obtained in this study can be helpful to pedestrian management on the stairs and the validation of stair evacuation models.